-6.3(2y+5)-2.5(4y-6)=

Simple and best practice solution for -6.3(2y+5)-2.5(4y-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6.3(2y+5)-2.5(4y-6)= equation:


Simplifying
-6.3(2y + 5) + -2.5(4y + -6) = 0

Reorder the terms:
-6.3(5 + 2y) + -2.5(4y + -6) = 0
(5 * -6.3 + 2y * -6.3) + -2.5(4y + -6) = 0
(-31.5 + -12.6y) + -2.5(4y + -6) = 0

Reorder the terms:
-31.5 + -12.6y + -2.5(-6 + 4y) = 0
-31.5 + -12.6y + (-6 * -2.5 + 4y * -2.5) = 0
-31.5 + -12.6y + (15 + -10y) = 0

Reorder the terms:
-31.5 + 15 + -12.6y + -10y = 0

Combine like terms: -31.5 + 15 = -16.5
-16.5 + -12.6y + -10y = 0

Combine like terms: -12.6y + -10y = -22.6y
-16.5 + -22.6y = 0

Solving
-16.5 + -22.6y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '16.5' to each side of the equation.
-16.5 + 16.5 + -22.6y = 0 + 16.5

Combine like terms: -16.5 + 16.5 = 0.0
0.0 + -22.6y = 0 + 16.5
-22.6y = 0 + 16.5

Combine like terms: 0 + 16.5 = 16.5
-22.6y = 16.5

Divide each side by '-22.6'.
y = -0.7300884956

Simplifying
y = -0.7300884956

See similar equations:

| 5x+9=2x+45 | | 4y-2y+5y-46=126 | | -17(-4+16)= | | v=nr*2n | | 3(y+10)+2y-5=0 | | 9x-38=20x+5 | | 22.33-x=32 | | 31/3x41/6 | | -2(6w-6)+6w=8+2(3w-7) | | 18(-1x+-2)-4(-9+3x)=-14 | | 4t^2+t-60=0 | | 5y+(3y-25)=47 | | 1.3x+4.4=.07x-0.52 | | M=s-c | | -2.5(y-10)-0.166= | | -x+9-4x=-31 | | (5X^-2Y^5/4X^6Y^-3)^-2 | | -(x+4)=3 | | X+5-8x=16 | | 0.13(x+40)+0.4(x+25)=-19.25 | | 3/8k=3/2 | | 4(y+1)=-2(4y-5)+3y | | 4.7-n=4.7 | | -3k-4=k+16 | | 5x-2=x+20 | | 3x-21=o | | 20x-20x-43=43 | | -5(-8x+5)-5x=1 | | w-4+4(3w+1)=-3(w+6) | | 0.7*n=1 | | mx=3m+2x+x | | 7p=8p+1 |

Equations solver categories